Intracoronary Infusion of Autologous CD133+ Cells in Myocardial Infarction and Tracing by Tc99m MIBI Scintigraphy of the Heart Areas Involved in Cell Homing - Ubaidullo Kurbonov; Abdusamad Dustov; Alisher Barotov; Murtazokul Khidirov; Giesidin Mirojov; Zikrie Rahimov; Navjuvon Navjuvonov; Eraj Rizoev; Nasim Olimov; Alijon Goibov; Bakhtovar Karim-Zade; Mukim Rakhmatov; et al. (Stem Cells International)
CD133 mesenchymal cells were enriched using magnetic microbead anti-CD133 antibody from bone marrow mononuclear cells (BMMNCs). Flow cytometry and immunocytochemistry analysis using specific antibodies revealed that these cells were essentially 89 ± 4% CD133+ and 8 ± 5% CD34+. CD133+/CD34+ BMMNCs secrete important bioactive proteins such as cardiotrophin-1, angiogenic and neurogenic factors, morphogenetic proteins, and proinflammatory and remodeling factors in vitro. Single intracoronary infusions of autologous CD133+/CD34+ BMMNCs are effective and reduce infarct size in patients as analyzed by Tc99m MIBI myocardial scintigraphy. The majority of patients were treated via left coronary artery. Nine months after cell therapy, 5 out of 8 patients showed a net positive response to therapy in different regions of the heart. Uptake of Tc99 isotope and revitalization of the heart area in inferoseptal region are more pronounced (P=0.016) as compared to apex and anterosptal regions after intracoronary injection of the stem cells. The cells chosen here have the properties essential for their potential use in cell therapy and their homing can be followed without major difficulty by the scintigraphy. The cell therapy proposed here is safe and should be practiced, as we found, in conjunction with scintigraphic observation of areas of heart which respond optimally to the infusion of autologous CD133+/CD34+ BMMNCs.